2010
DOI: 10.1371/journal.pone.0013480
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Novel Big Defensin from Clam Venerupis philippinarum

Abstract: Antimicrobial peptides (AMPs) are important mediators of the primary defense mechanism against microbial invasion. In the present study, a big defensin was identified from Venerupis philippinarum haemocytes (denoted as VpBD) by RACE and EST approaches. The VpBD cDNA contained an open reading frame (ORF) of 285 bp encoding a polypeptide of 94 amino acids. The deduce amino acid sequence of VpBD shared the common features of big defensin including disulfide array organization and helix structure, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…[16]. BLAST analysis of all the 3226 EST sequences revealed that one EST of 508 bp was highly similar to the previously identified SABL.…”
Section: Cloning Of the Full-length Cdna Of Vpsabl By Cdna Library Anmentioning
confidence: 61%
See 1 more Smart Citation
“…[16]. BLAST analysis of all the 3226 EST sequences revealed that one EST of 508 bp was highly similar to the previously identified SABL.…”
Section: Cloning Of the Full-length Cdna Of Vpsabl By Cdna Library Anmentioning
confidence: 61%
“…The salinity for the supplied seawater was kept at 30&. The performance of V. anguillarum challenge experiment was according to our previous work [16,17]. There were five replicates for each challenge point and control group.…”
Section: Clams and Bacterial Challengementioning
confidence: 99%
“…Allam et al (2006) reported a rapid increase (within 72 h) of circulating hemocytes in V. philippinarum after injection of Vibrio tapetis and V. anguillarum. In general, expression of marine mollusk defensin transcripts is known to be induced by bacterial challenges (Adhya et al, 2012;De Zoysa et al, 2010;Rosa et al, 2011;Zhao et al, 2007Zhao et al, , 2010. However, there are some reports of decreased transcriptional responses of mollusk defensins against bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…A Manila clam EST homologous to C. gigas defensin2 was identified through large scale EST sequencing of the cDNA library constructed from clam hemocytes (Zhao et al, 2010). To generate the full-length cDNA of VpDef, two reverse primers P1 and P2, and two forward primers P3 and P4 (Table 1), were designed based on the EST sequence.…”
Section: Cdna Cloning and Sequence Analysis Of Vpdefmentioning
confidence: 99%
See 1 more Smart Citation